SPECIFIC ASPECTS OF STRATEGIC ENTREPRENEURSHIP IN FAMILY COMPANIES AND NON-FAMILY COMPANIES - Arsic, Sinisa M (Journal of process management and new technologies, 2017)
The paper presents a theoretical analysis of the strategic innovation attributes that are represented in family companies, and the paper cross examinates a significant number of references dealing with this topic. In the reviewed literature, one aspect is usually imposed as a basis for comparison and evaluation of innovation in family companies, and it is "strategic entrepreneurship" (functional link of strategy and idea generation from an individual or a team of people). The above-mentioned aspect is not analyzed in detail in the case of intrapreneurship in non-family companies. The aim of this paper is in realization of high-quality supplements or conclusions from the literature dealing with strategic entrepreneurship. The originality of this work lies in the analysis and comparison of family and non-family companies, by amending the variables that define strategic enterpreneurship. Thus, it allowes the applicability of the same variables in the case of analysing  family and non-family companies, and also identifies variables unique to a family company.